The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/pssc.200461340
|View full text |Cite
|
Sign up to set email alerts
|

Nitride micro‐display with integrated micro‐lenses

Abstract: We report progress in control of the emission from both parallel-addressed and matrix-addressed micro-array light-emitting diodes (micro-LEDs), using integrated micro-lenses. The integrated matrix-addressed device consists of a 128 × 96 element array with 470 nm emission, aligned to a 128 × 96 element sapphire micro-lens array. The lenses have a diameter of 12 µm, a centre height of 1.8 µm and a measured focal length of 8 µm. The root-mean-square (r.m.s.) roughness of the lenses, as measured by atomic force mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The homogeneity of the illumination can also be improved with a lens array [19]. Similar scheme was used in wireless communications [20] and in display optics [21,22]. We show in this paper that, with a mask, a lens array and an additional large numerical aperture lens, larger-sized PCs can be conveniently fabricated.…”
Section: Principle and Experimental Setupmentioning
confidence: 85%
“…The homogeneity of the illumination can also be improved with a lens array [19]. Similar scheme was used in wireless communications [20] and in display optics [21,22]. We show in this paper that, with a mask, a lens array and an additional large numerical aperture lens, larger-sized PCs can be conveniently fabricated.…”
Section: Principle and Experimental Setupmentioning
confidence: 85%
“…In a nanopillar micro-LED, each nanopillar acts as a point light source and hence its emission can be collimated by a nanoscale parabolic lens [17]. This approach deviates from other microlens work [18,19] in that the overall profile of the lens array is nearly flat compared to the dimension of the microLED. As a result, the proposed nanoscale parabolic lenses do not pose an additional constraint on the spatial resolution of the display.…”
Section: Introductionmentioning
confidence: 99%
“…The divergent nature of LED emission results in inevitable crosstalk between adjacent pixels. In our previous works on micro-LED arrays, it was found that the light cone from adjacent pixels tend to merge at higher driving currents due to Lambertian dispersion [9], making it impossible to resolve individual pixel points. The fiber bundle eliminates crosstalk by virtue of its limited acceptance cone, ensuring that the output pattern is sharp and fully resolvable.…”
Section: Introductionmentioning
confidence: 99%